EVSS- electro tactile vestibular substitution system as a new vestibular rehabilitation approach: A pilot study - Aliakbar Nasr-Esfahani; Parisa Rasulifard; Elham Rajabpour; Mohammadhussein Nilforoush; Mahsa Sepehrnejad (Vesnu Publications, 2012)
Introduction: Using conventional methods of vestibular rehabilitation such as adaptation and habituation exercises is a management strategy for patients with bilateral vestibular loss due to aminoglycoside ototoxicity so far. Previous studies shown EVSS- electrotactile vestibular substitution system- might have an important role in the rehabilitation process for these patients. This study investigated the effect of this therapeutic modality as a pilot study. Materials and Methods: In this study, 10 cases (6 males, 4 females) with bilateral vestibular loss were rehabilitated by EVSS. This approach was conducted in 10 sessions, 20 minutes per session (two sessions per day). Sensory organization test (SOT) and Dizziness handicap Inventory (DHI) were performed before and after treatment (at the first day of post-treatment period).  Difference between the groups before and after treatment was analyzed by t-test using SPSS software (ver. 16). Results: After 10 treatment sessions, all subjects had significant difference in score of SOT and DHI (P < 0.05). Less falling (5th stage of SOT) was seen after treatment sessions (P < 0.05). Subjects could maintain their straight posture in Romberg position, with closed eyes and on a soft surface (P < 0.05) and their movements were also more uniform and their gait was more stable (P < 0.05). Conclusion: The results show recuperation of subjects following EVSS that indicate probable sensory systems substitution in order to manage vestibular disorders. Keywords: Vestibular rehabilitation, Electrotactile vestibular substitution system (EVSS), Balance disorders